Communication in Intercultural Marriage: A Chinese-Indonesian Bride in A Taiwanese Family - Wijaya Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
The number of intercultural marriages is increasing globally over time. In Indonesia, around 10% of the total population of Indonesian did lifetime migration which implies the high possibility of intercultural marriage. The couple must have several problems with communication due to different cultural and educational backgrounds. Therefore in this study, the researcher intends to find out the communication problems related to language and culture between a Chinese-Indonesian wife and a Taiwanese husband, and how they manage the problems using the communication competence they develop over cultural differences. The findings suggest that the wife sometimes has language misinterpretation with her parents-in-law due to the inability to speak Taiwanese. In relevance to culture, the wife employs sungkan on many occasions, while the husband is affected by the patriarchal culture and money-saving habits of the Taiwanese. Knowledge and skills are essential for the couple to manage their communication problem.Key words: Intercultural marriage; intercultural communication; communication competence; communication problems